Sanitary conduct in coping with COVID-19 (Research, Society and Development, 2021)
The cheapest and most necessary protection measure for non-dissemination of the virus is the use of personal protective equipment (such as masks), and proper hygiene, these precautions are valid for both hospital and domestic environments. This work intends to evaluate articles that talk about the hygiene of places that serve patients with COVID 19, in order to present the importance of hygiene and not to contaminate professionals, patients and companions so that it can positively assist in research. Data were collected using the scientific bases: Latin American and Caribbean Literature in Health Sciences (LILACS), National Library of medicine (PUBMED), PERIODICOS, SCIENCE DIRECT, Virtual Health Library - (BVS), Scientific Eletronic Library Online (SCIELO), Cochrane Library, HighWire Press, Scopus and Elsevier. A total of 22 articles (table 1) were found in the scientific bases: Latin American and Caribbean Literature in Health Sciences (LILACS), National Library of medicine (PUBMED), PERIODICOS, SCIENCE DIRECT, Virtual Health Library - (BVS ), Scientific Eletronic Library Online (SCIELO), Cochrane Library, HighWire Press, Scopus and Elsevier. The following descriptors were used: HYGIENIZATION, DECONTAMINATION, SARS-COV-2, COVID 19 in English, Portuguese and Spanish. Where we obtained the articles described below in table 1 and discussed in the form of topics related to the theme. In this work we can see that there is a need for hygiene not only to avoid contagion in patients, but also in professionals in the field. Where since the beginning of the pandemic, there have been a large number of cases, making them join the risk group. We observed that each service has a peculiarity of hygiene and service organization.